Analytical study on a turbine housing with inner insulation structure for rapid catalyst light-off. Issue 1 (1st April 2022) - Kitamura, T; Hoshi, T; Ebisu, M
Abstract: The analytical study on a turbine housing with inner insulation structure has been conducted for rapid light-off of a catalyst unit, which is located at the downstream side of turbochargers. CHT (Conjugate Heat Transfer) calculations, working for simulating heat transfer with mutual dependence between solid structures and fluid, are applied to the turbocharger including the turbine section, the bearing housing and the catalyst unit to evaluate the time reduction for activation of the catalyst unit. Feasible inner-insulation structures to be installed in the turbine housing have been also designed. Eventually, the inner-insulated turbine housing has been proven highly effective for rapid catalyst light-off.